Produção de sorvetes com características simbióticas e avaliação da sobrevivência de Lactobacillus paracasei em condições gastrointestinais simuladas - Frighetto, Juan Marcel (2012)
Research has demonstrated that ice cream may be an appropriate vehicle for probiotic microorganisms and some prebiotic substances. Also, the widespread acceptance of ice cream, both by infantile, juvenile and adult public as well as by the elderly, and the increase of its consumption encourage the continuation of applied studies for developing functional ice cream. However, current researches refer mostly to the viability of probiotic micro-organisms during the product s storage period, while references of the survival of these micro-organisms under gastrointestinal conditions, essential to confirm the product efficacy, occur less frequently. The aim of this study was to develop symbiotic ice creams and to investigate the survival of Lactobacillus paracasei Lpc-37 under simulated gastrointestinal conditions. Four ice cream samples were developed, one probiotic and three symbiotic (these, including Lactobacillus paracasei Lpc-37 and inulin, oligofructose or polydextrose). The ice cream samples were analyzed for physical (overrun), chemical and nutritional (pH, lactic acid, total solids, ash, protein, fat, carbohydrates and calorie level) and sensory characteristics (acceptability, preference, consumption frequency and taste and flavor intensity). Microbiological analysis comprised counts of viable probiotic micro-organisms in ice cream and its survival under simulated gastrointestinal conditions, carried out monthly during the period of 90 days. L. paracasei LPC-37 showed resistance to technological processes for in the obtention of ice cream, stability during the storage of product and resistence in vitro to the stress in the gastrointestinal tract. Inulin and polydextrose played a protective activity for probiotic micro-organism, elevating their final survival rates under simulated gastrointestinal conditions. The soluble fibers added into the ice cream contributed to a proportional fat reduction and consequently decreasing calorie levels. Effects on sensory attributes, when occurred, ensured the prominence of ice cream with inulin added, followed by those with polydextrose added. Therefore, the inclusion of L. paracasei Lpc-37 in ice cream shows technological viability and ability to do its functional role in the colon, estimated in vitro. Additionally, inulin and polydextrose improve functional, nutritional and sensory properties in symbiotic ice cream. Results extend the possibilities of development of functional foods, as the developed ice cream meets the consumer s expectations for attractive and healthy products